Mechanical Characterization of Polypropylene - Wood Flour Composites - Nuñez, A. J. (2003)
The mechanical performance of different wood flour/polypropylene (PP) composites with interface modifications was compared. Wood flour was incorporated into the matrix after esterification with maleic anhydride (MAN) or without any modification but with the addition of a compatibilizing agent [maleic anhydride-polypropylene copolymer (PPMAN)] to modify the polymer-filler interaction. Composites were prepared by injection molding with different concentrations of wood flour. Mechanical properties (except Young's modulus) were not improved either by the wood flour chemical modification or by the use of PPMAN. However, both compatibilization methods were successful in improving the dispersion of the wood flour in the PP matrix. Creep behavior of composite samples was improved by the addition of PPMAN, whereas the composites prepared from MAN-treated wood flour showed larger deformations than composites made with untreated particles.